Autonomous Mobile Robot with Arm for Tomato Harvesting Using Raspberry Pi and Computer Vision - Zamanbek Azil (Theoretical Hypotheses and Empirical Results, 2024)
This project introduces the development of an autonomous mobile robot equipped with a robotic arm, aimed at efficiently harvesting tomatoes. The robot utilizes a Raspberry Pi as its central processing unit, paired with a camera module for computer vision-based detection of tomatoes. The robotic arm, controlled by precise servo motors, is engineered to accurately locate and pick ripe tomatoes. This multidisciplinary project integrates computer vision techniques, robotics, and embedded systems to present an innovative solution for automating the labor-intensive task of tomato harvesting. Agriculture, a vital industry, faces significant challenges such as labor shortages and the need for increased efficiency in harvesting operations. Traditional methods of tomato harvesting are labor-intensive and prone to inefficiencies, leading to increased costs and potential crop damage. This project aims to address these challenges by developing an autonomous system capable of performing the task with minimal human intervention, thereby reducing labor costs and improving overall productivity. The system is composed of several key components: a Raspberry Pi, a camera module, a robotic arm with servo motors, a mobile platform, and a suite of computer vision algorithms. The Raspberry Pi serves as the brain of the robot, handling image processing, decision-making, and the control of the robotic arm. The camera module captures real-time images of tomato plants, which are then processed by computer vision algorithms implemented on the Raspberry Pi. These algorithms are designed to detect ripe tomatoes by performing color segmentation, contour detection, and feature extraction. The precise location of each detected tomato is determined, enabling the robotic arm to accurately target and pick the fruit. The robotic arm is controlled through a series of steps involving target position calculation, inverse kinematics, and servo motor control. Once a tomato is detected and its location is established, the target position for the robotic arm’s end effector (gripper) is calculated. Inverse kinematics algorithms compute the necessary angles for each servo motor to reach the target position. The Raspberry Pi then sends pulse-width modulation (PWM) signals to the servo motors to adjust their angles accordingly, guiding the arm to the tomato. Upon reaching the tomato, the gripper closes to grasp it and then opens to release it into a collection container. Mobility is a critical aspect of the robot’s functionality, allowing it to navigate through tomato fields autonomously. Several navigation strategies are considered, including line following, GPS-based navigation, and vision-based navigation. These methods ensure that the robot can traverse the field, avoid obstacles, and locate tomato plants efficiently. The hardware implementation involves integrating the Raspberry Pi with the camera module, servo motors, and mobile platform. The Adafruit ServoKit library facilitates the control of the servo motors through the Raspberry Pi, while the camera module connects via the CSI (Camera Serial Interface) connector. Software development focuses on implementing computer vision algorithms using the OpenCV library and developing control logic using the Python programming language. Testing in both controlled and field environments demonstrates the robot’s capability to detect and pick ripe tomatoes with high accuracy under various lighting conditions. The robotic arm’s precise movements minimize damage to the tomatoes and surrounding plants, while the mobile platform’s navigation capabilities enable effective traversal of different terrains and obstacles. This project underscores the potential of robotics and computer vision to revolutionize the agricultural sector. The autonomous tomato harvesting robot offers a viable solution to labor shortages, increases productivity, and reduces crop losses. Future work will involve refining the detection algorithms, optimizing the robotic arm design, and incorporating machine learning techniques to enhance adaptability and decision-making. Advanced navigation algorithms will also be developed to enable the robot to operate in more complex and dynamic environments. This project lays the foundation for further research and development in agricultural automation, paving the way for a more sustainable and efficient future in farming.